INSTILLING RELIGIOUS MODERATION: A STUDY OF PAI AND ETHICS LEARNING AT SD ANGKASA 3 SULTAN HASANUDDIN AIR BASE - Khairul Saleh; Syamsuddin (LP2M IAIN Sultan Amai Gorontalo, 2026)
As a pluralistic nation, Indonesia continues to face the challenge of fostering harmony amid religious and cultural diversity. Schools play a vital role in cultivating inclusive values. This study examines how religious moderation values are internalized in Islamic Religious Education and Character (PAI dan Budi Pekerti) at SD Angkasa 3 Lanud Sultan Hasanuddin, a primary school with a diverse student population. Although national policies promote religious moderation, empirical studies at the elementary level remain scarce. The research aims to analyze how religious moderation values are integrated into learning, identify factors that support or hinder the process, and assess their influence on students' social behavior. Using a qualitative descriptive method, data were gathered through interviews, observations, and documentation involving teachers, the principal, and students. Results show that values such as tolerance (tasamuh), justice (i'tidal), and balance (tawazun) are instilled through both curriculum content and daily routines. Teachers apply contextual strategies and act as role models in inclusive classrooms. Nonetheless, challenges appear among younger students who struggle with abstract concepts. The study concludes that structured learning and real-life school culture successfully promote moderation. This research offers valuable insights for educators and policymakers to strengthen tolerance education from an early age.